2003
DOI: 10.1046/j.1472-8206.2003.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

A QSAR analysis to explain the analgesic properties of Aconitum alkaloids

Abstract: Aconitum roots are traditionally prescribed for the management of different types of painful affections in Asiatic countries. A quantitative structure-activity relationship (QSAR) analysis was performed to study the effect of chemical substitutes in the analgesic potency of alkaloids available in Chinese Aconitum roots. Using the CAChe program package for biomolecules, molecular modelling was performed in 12 alkaloids previously tested in a model of acetic acid-induced writhing in rats. The ED50 (micromol/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 10 publications
1
46
0
Order By: Relevance
“…In the recently reported QSAR analysis of 12 Aconitum alkaloids [7], the authors have identified a number of structural characteristics, chemical manipulation of which might result in both an increase of analgesic potency and a limitation of toxicity. Mono-parameter equations consisting of reactivity index, heat of formation, total, electronic and steric energies, molecular weight and core-core repulsion were selected as statistically significant ones.…”
Section: Physchem Bidescriptor Model (E)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the recently reported QSAR analysis of 12 Aconitum alkaloids [7], the authors have identified a number of structural characteristics, chemical manipulation of which might result in both an increase of analgesic potency and a limitation of toxicity. Mono-parameter equations consisting of reactivity index, heat of formation, total, electronic and steric energies, molecular weight and core-core repulsion were selected as statistically significant ones.…”
Section: Physchem Bidescriptor Model (E)mentioning
confidence: 99%
“…Likewise, toxicity of the alkaloids has been investigated by modifying certain functional groups. Further, a careful literature search has revealed that investigation of diterpene alkaloids by means of QSAR approach has received very little attention and only recently has an attempt been made to perform a QSAR analysis of the analgesic properties for twelve Aconitum alkaloids [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hence only recently a QSAR analysis of the analgesic and anesthetic properties for 12 Aconitum alkaloids (Bello-Ramirez et al, 2003 and 19 nAChR antagonists (Turabekova and Rasulev, 2005) have been reported. The toxicity/activity data available for these alkaloids and the intriguing sodium channels modulation exhibited (openers and blockers in one homologous series) makes them very interesting targets for molecular modelling studies.…”
Section: Introductionmentioning
confidence: 99%
“…3 The C 19 -diterpenoid alkaloids are the major bioactive compounds in the tubers of Aconitum carmichaelii and have been widely used due to their predominant analgesic, antipyretic, anti-rheumatoid arthritis, and anti-inflammation effects. 4,5 To further study the biological activities of these alkaloids and to control the quality of this traditional Chinese medicine and its extract, a large quantity of pure compounds are urgently needed. Therefore, the development of an efficient method for the separation and purification of C 19 -diterpenoid alkaloids from Aconitum carmichaelii is required.…”
Section: Introductionmentioning
confidence: 99%